The Islamist Challenge: Between "Modernization" and Intimidation - al-Ahsan, Abdullah (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Islamist Challenge: Between "Modernization" and Intimidation